About the Rationality of Acting in Max Weber’s Theory - Polaczuk, Paweł (Studia Warmińskie, 2011)
The article concerns the rationality of acting in Max Weber’s theory of action. The taken attempt of reconstruction of the relation between action and the rationality refers to general types of action and of types of public action. The following regularities of Weber of the presentation are becoming apparent: first, special significance of action of the intentional-rational type, so which is based on the calculation of means because of the purpose. Such action contains structures of the meaning analogous to mathematical-logical what understanding real action enables. Action of the intentional-rational type constitutes the construct on which types of public action are relying. Weber is increasing meaning of intentional-rational elements in these types of action (is rationalizing them) and the number and the significance of trademarks proving about public directing action. This way contemplated clean types of public action constitute the foundation for the rationality of the social orders. Until the end however thinking of the structure covered with drawings here is showing that the system rationality is reducing public informing acting, getting it for rational action because of the purpose.